2012
DOI: 10.4067/s0717-92002012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Determinación de la tendencia espacial de los puntos de calor como estrategia para monitorear los incendios forestales en Durango, México

Abstract: SUMMARYIn Mexico hotspots detection is a useful tool to provide opportune information on forest fire fighting. The aim of this study was to assess hotspots for the period of 2001-2010 in various ecozones in the north of México. The study area was divided into 1,343 physiographical units, and quantitative indices of clustering were calculated using the Getis-Ord statistics. As a statistical test on the validity of the clustering, a p-value test was carried out. Results revealed that the locations of hotspots sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In the NW region, the highest FDI values were observed for Temperate Forests, agreeing with previous studies in the region (e.g., Avila-Flores et al 2010a;Avila-Flores et al 2010b;Pérez-Verdin et al 2013a;2013b;Pérez-Verdin et al 2014;Pompa-García and Hernández González 2012), that found that most of the fires in Durango State occurred on conifer and hardwood temperate forest.…”
Section: Observed Fdi Trends By Vegetation Types and Regionssupporting
confidence: 91%
“…In the NW region, the highest FDI values were observed for Temperate Forests, agreeing with previous studies in the region (e.g., Avila-Flores et al 2010a;Avila-Flores et al 2010b;Pérez-Verdin et al 2013a;2013b;Pérez-Verdin et al 2014;Pompa-García and Hernández González 2012), that found that most of the fires in Durango State occurred on conifer and hardwood temperate forest.…”
Section: Observed Fdi Trends By Vegetation Types and Regionssupporting
confidence: 91%
“…In Pompa-García & González (2011) evaluated the fires that occur in the state of Durango and Mexico to detect which fires had greater proliferation, discovered that in the ecosystems where trees such as pine, oak and grasslands proliferate, different behaviors were detected. The authors detected that a fire where there was pine and oak this was presented in a group, while in areas where there is grassland, the fire occurs randomly.…”
Section: Fire Identification: Proposals In the State Of The Artmentioning
confidence: 99%
“…),Pompa- García & González (2011),Lawrence & Zhang (2019), Hernandez-Hostaller, (2017)Zhao (2022) andParajuli et al (…”
mentioning
confidence: 95%
“…On the other hand, the other challenge that exists is the early detection of a fire, as well as the prediction of its evolution to avoid a rapid spread. Some points that was analyzed from the information collected previously in the works of González-Gutiérrez et al (2019), Pompa-García & González (2011), Lawrence & Zhang (2019), Hernandez-Hostaller, ( 2017) Zhao (2022) and Parajuli et al (2020) is that forest fire detection systems should consider the following elements.…”
Section: Wildfire Identification Technologiesmentioning
confidence: 99%